Cover Feature: A Benzocaine‐Induced Local Near‐Surface pH Effect: Influence on the Accuracy of Voltammetric Cocaine Detection (Analysis & Sensing 1/2021). Issue 1 (22nd December 2020) - de Jong, Mats; Sleegers, Nick; Schram, Jonas; Daems, Devin; Florea, Anca; De Wael, Karolien
Abstract : The Cover Feature shows that the voltammetric detection of cocaine is affected by the presence of benzocaine, a common adulterant in street samples. Benzocaine causes a large shift and current drop of the cocaine signal, resulting in a clouded and false negative analysis. This behaviour was shown to be a consequence of a benzocaine‐induced near‐surface pH effect. This local pH change was evidenced and monitored by multiple electrochemical and fluorescence approaches by using a green fluorescent fluorophore. More information can be found in the Full Paper by K. De Wael and co‐workers .